Integrating IoT-Based Learning Media to Enhance Science Literacy and 21stCentury Skills in Elementary Education: A Systematic Literature Review - Dania Dwi Ramadhani; Fatih Raisa Fajriana; Lina Mariana Putri Samingan; Yeni Rakhmawati; Alaa Abdelkader Abdelmonem Abdelkader (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2026)
This study addresses the challenge of organic waste management arising from the Makan Bergizi Gratis (MBG) program in elementary schools, where inadequate waste processing systems limit both environmental sustainability and contextual learning opportunities. To respond to this issue, the study aims to examine the role of Internet of Things (IoT)-based learning media in enhancing elementary school students’ science literacy and 21st-century skills, as well as to identify its pedagogical benefits and implementation constraints. A Systematic Literature Review (SLR) was conducted by screening 200 articles published between 2021 and 2026 using Google Scholar through the Publish or Perish application. Based on predefined inclusion criteria focusing on IoT-based STEM learning, elementary education contexts, and learning outcomes related to literacy and 21st-century skills 18 articles were identified as relevant, and 9 peer-reviewed studies were selected for detailed analysis. The findings indicate that integrating IoT into organic waste management enhances student engagement through observation, real-time data collection, and analysis. Science literacy improved through contextual understanding of concepts, while 21st-century skills, particularly critical thinking, creativity, and collaboration, were fostered through problem-based and data-driven learning. However, the effectiveness of IoT-based learning media is influenced by infrastructure readiness and teachers’ technological competence. This review highlights IoT-based learning media as a strategic and sustainable innovation for supporting contextual science education in elementary schools.